Global Strategic Management - Collins Sylvie C; Mellahi Kamel; Ogden Jane (Oxford University Press, 2005)
This book offers a trully global, as opposed to multinational, perspective on strategy, covering both traditional strategic management topics and new topics such as corporate social responsibility.Preface, Acknowledgements, Introduction, Introduction to Global Strategic Management, Learning Outcomes, Opening Case Study: IKEA, Global Strategic Analysis, Global Business Environment: The External Macro Environment, The World Trade Organization and September 11 Events and the Brazilian Embraer, Global Business Environment: The Industry Environment, The Rise of the Internet and the Fall of Boo.com, Corporate Social Responsibility and Stakeholder Analysis, Two Crises Influence the Strategy of Royal Dutch/ Shell, Analysis of the Internal Environment, Global Strategic Development, Managing the Internationalization Process, International Strategic Alliances: Partnership and Cooperation, The Subsidiary - Level Strategy, Headquarter - Level Strategy, Global Strategic Implementation, Global Structures and Design, Global Management of Change, Global Strategic Control, Index.